Up and running: integrating information technology and the organization - Walton, Richard E. (Harvard Business School P. BostonUS, 1989)
Focuses on the effective implementation of advanced information technology (IT) in organizations. Presents case histories from 19 separate entities. Reports on both positive and negative examples to demonstrate good practice with IT systems used by workers, professionals, and managers for material resource planning, computer-integrated manufacturing (CIM), databases management, decision support, expert analysis, and end-user computing.